OPTIMASI BIAYA, FUNGSI DAN NILAI DESAIN GEDUNG ASRAMA PONDOK PESANTREN "QUEEN AFLAH" SIDOARJO - Christiono Utomo; Anita Trisiana (Jurnal Teknobisnis, 2005)
Pesantren "Queen Aflah" Project was built to provide Islamic education service. Development of the project required funds of Rp. 13.721.940.000. This project needs an analysis to determine the existence of expense which is not needed, to assist the process improvement, and to increase the design value. There are some important research questions which have to be solved, such as: how to apply the function analysis for determining which design has optimal pursuant to specified function, what expense is needed at building- construction project predominated by primary function or secondary function, and how much function of element is needed. Function Analysis System Technique (FAST) method was used to show graphically the relationship between depending function of design component, herein after matrix of expense function function cost matrix) was used to determine the value from each component of design, expressed in percentage. Evaluated function in CM (Cost/Worth) ratio was used to measure that there was expense which was not needed and showed cost optimization to the desired function. Results of analysis indicated that the wall work at bathroom interior got Cost/Worth = 2,24. This meant that effective expense was insufficient to fulfill the function of the planned design. Cost allocation which was not needed, was specimen component which belonged to brick arrangement function. This was because 7,584% of expense was used for brick arrangement secondary function.